Correlation of serum levels and gene expression of tumor necrosis factor-α-induced protein-8 like-2 with Parkinson disease severity - Kouchaki, Ebrahim; Daneshvar Kakhaki, Reza; Tamtaji, Omid Reza; Dadgostar, Ehsan; Behnam, Mohammad; Zaribaf, Alireza; Nikoueinejad, Hassan; Akbari, Hossein; Asemi, Zatollah (Metabolic brain disease, 2018)
Different immune-mediated mechanisms involved in the pathogenesis of Parkinson disease (PD) as a neurodegenerative and inflammatory disease. According to our knowledge, there is no report evaluating Tumor necrosis factor-α-induced protein-8 like-2 (TIPE2), a cytokine maintaining immune homeostasis, in PD. We analyzed the correlation of the serum levels and circulatory gene expression of TIPE2 with severity of PD. In this case-control study, 43 patients with PD and 40 healthy subjects were enrolled. The diagnosis of PD was performed byclinical diagnostic criteria of the UK Parkinson’s Disease Society Brain Bank. The severity of PD was evaluated by modified Hoehn and Yahr (H and Y) scale. Serum levels and gene expression of TIPE2 were assessed by Elisa and real time PCR, respectively. The mean serum levels and gene expression of TIPE2 in patients with PD did not have significant difference compared to healthy subjects. Linear multiple regression analysis showed that increased serum levels of TIPE2 are positively related to age and severity of PD ( P ≤ 0.0001). In addition, the gene expression of TIPE2 was found to be associated with age ( P < 0.0001). Our study showed that the serum levels of TIPE2 and its gene expression might be important prognostic biomarkers of PD.